Feasibility of a traditional and teletreatment approach to mirror therapy in patients with phantom limb pain: a process evaluation performed alongside a randomized controlled trial. (October 2019) - Rothgangel, Andreas; Braun, Susy; Smeets, Rob; Beurskens, Anna
Objective: To evaluate the delivery, acceptance and experiences regarding a traditional and teletreatment approach to mirror therapy as delivered in a randomized controlled trial. Design: Mixed methods, prospective study. Setting: Rehabilitation centres, hospital and private practices. Subjects: Adult patients with phantom pain following lower limb amputation and their treating physical and occupational therapists. Interventions: All patients received 4 weeks of traditional mirror therapy ( n  = 51), followed by 6 weeks of teletreatment ( n  = 26) or 6 weeks of self-delivered mirror therapy ( n  = 25). Main measures: Patient files, therapist logs, log files teletreatment, acceptance questionnaire and interviews with patients and their therapists. Results: In all, 51 patients and 10 therapists participated in the process evaluation. Only 16 patients (31%) received traditional mirror therapy according to the clinical framework during the first 4 weeks. Between weeks 5 and 10, the teletreatment was used by 14 patients (56%) with sufficient dose. Teletreatment usage decreased from a median number of 31 (weeks 5–10) to 19 sessions (weeks 11–24). Satisfactory teletreatment user acceptance rates were found with patients demonstrating higher scores (e.g. regarding the usefulness to control pain) than therapists. Potential barriers for implementation of the teletreatment perceived by patients and therapists were related to insufficient training and support as well as the frequency of technical problems. Conclusion: Traditional mirror therapy and the teletreatment were not delivered as intended in the majority of patients. Implementation of the teletreatment in daily routines was challenging, and more research is needed to evaluate user characteristics that influence adherence and how technology features can be optimized to develop tailored implementation strategies.